Neuronal Cholesterol Accumulation Induced by Cyp46a1 Down-Regulation in Mouse Hippocampus Disrupts Brain Lipid Homeostasis - Ayciriex, Sophie; Djelti, Fathia; Alves, Sandro; Regazzetti, Anne; Gaudin, Mathieu; Varin, Jennifer; Langui, Dominique; Bièche, Ivan; Hudry, Eloise; Dargère, Delphine; Aubourg, Patrick; Auzeil, Nicolas; et al. (Frontiers in Molecular Neuroscience, 2017)
Impairment in cholesterol metabolism is associated with many neurodegenerative disorders including Alzheimer's disease (AD). However, the lipid alterations underlying neurodegeneration and the connection between altered cholesterol levels and AD remains not fully understood. We recently showed that cholesterol accumulation in hippocampal neurons, induced by silencing Cyp46a1 gene expression, leads to neurodegeneration with a progressive neuronal loss associated with AD-like phenotype in wild-type mice. We used a targeted and non-targeted lipidomics approach by liquid chromatography coupled to high-resolution mass spectrometry to further characterize lipid modifications associated to neurodegeneration and cholesterol accumulation induced by CYP46A1 inhibition. Hippocampus lipidome of normal mice was profiled four weeks after cholesterol accumulation due to Cyp46a1 gene expression down- regulation at the onset of neurodegeneration. We showed that major membrane lipids, sphingolipids and specific enzymes involved in phosphatidylcholine and sphingolipid metabolism, were rapidly increased in the hippocampus of AAV-shCYP46A1 injected mice. This lipid accumulation was associated with alterations in the lysosomal cargoe, accumulation of phagolysosomes and impairment of endosome-lysosome trafficking. Altogether, we demonstrated that inhibition of cholesterol 24-hydroxylase, key enzyme of cholesterol metabolism leads to a complex dysregulation of lipid homeostasis. Our results contribute to dissect the potential role of lipids in severe neurodegenerative diseases like AD.